(untitled) (Oratio Directa, 2024)
Friendship is one of the most valuable relationships for humans. In intercultural communication, friendship can be understood as a relationship between people from different cultural backgrounds and can produce positive changes in attitude, including greater cultural understanding, acceptance, and self-reflection. This qualitative descriptive study describes and explains friendship among lecturers at Universitas Bung Karno from the perspective of similarity-attraction theory. Data were collected from six participants through participatory observation and documentation. The study concludes that friendship within the lecturer group is built on shared values and beliefs, attitudes, cultural backgrounds, and interests, allowing the participants to complement one another despite their cultural differences.